Theranostics: Carbon Dots with Intrinsic Theranostic Properties for Bioimaging, Red‐Light‐Triggered Photodynamic/Photothermal Simultaneous Therapy In Vitro and In Vivo (Adv. Healthcare Mater. 6/2016). Issue 6 (March 2016) - Ge, Jiechao; Jia, Qingyan; Liu, Weimin; Lan, Minhuan; Zhou, Bingjiang; Guo, Liang; Zhou, Hangyue; Zhang, Hongyan; Wang, Ying; Gu, Ying; Meng, Xiangmin; Wang, Pengfei
Abstract : Water‐dispersible and red emissive carbon dots can simultaneously generate 1 O2 and heat (symbolized by the flame around the carbon dots) under 635 nm laser irradiation. As described by Y. Gu, P. Wang, and co‐workers on page 665, this unique property enables C‐dots to act as red light‐triggered theranostic agents for imaging‐guided photodynamic‐photothermal therapy in vivo.